Elastic scattering and the proton form factor - Carvalho, F.; Natale, A. A.; Zanetti, C. M. (World Scientific Publ Co Pte Ltd, 2006)
We use the QCD pomeron model proposed by Landshoff and Nachtmann to compute the differential and the total cross-sections for pp scattering in order to discuss a QCD-based approach to the proton form factor. This model is quite dependent on the experimental electromagnetic form factor, and it is not totally clear why this form factor gives good results even at moderate transferred momentum. We exchange the electromagnetic form factor by the asymptotic QCD proton form factor determined by Brodsky and Lepage (BL) plus a prescription for its low energy behavior dictated by the existence of a dynamically generated gluon mass. We fit the data with this QCD inspired form factor and a value for the dynamical gluon mass consistent with the ones determined in the literature. Our results also provide a determination of the proton wave function at the origin, which appears in the BL form factor.
Keywords: proton form factor; pp cross-section; dynamical gluon mass